2014
DOI: 10.1016/j.neuron.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel Mediates the Selective Rebalancing of Ion Channel Expression

Abstract: SUMMARY Ion channel gene expression can vary substantially among neurons of a given type, even though neuron-type-specific firing properties remain stable and reproducible. The mechanisms that modulate ion channel gene expression and stabilize neural firing properties are unknown. In Drosophila, we demonstrate that loss of the Shal potassium channel induces the compensatory rebalancing of ion channel expression including, but not limited to, the enhanced expression and function of Shaker and slowpoke. Using ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 34 publications
7
56
0
Order By: Relevance
“…We still do not understand the biological roles played by many of these channels, mainly because we have not yet developed a sufficient set of pharmacological tools. Gene knockout technology has advanced our understanding to some degree, but such approaches are not good surrogates for acute pharmacology experiments because compensatory expression of a second channel that can fulfill the role of the missing first is all too common, especially given the large number and redundancy of K + channels (35,36). This paper presents an assay called LFA, to identify inhibitors and activators of K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…We still do not understand the biological roles played by many of these channels, mainly because we have not yet developed a sufficient set of pharmacological tools. Gene knockout technology has advanced our understanding to some degree, but such approaches are not good surrogates for acute pharmacology experiments because compensatory expression of a second channel that can fulfill the role of the missing first is all too common, especially given the large number and redundancy of K + channels (35,36). This paper presents an assay called LFA, to identify inhibitors and activators of K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of specific ion channels in Drosophila has been shown to activate homeostatic transcriptional networks that act to balance excitability (Parrish et al, 2014;Ping and Tsunoda, 2012). In addition, the AZ T-bar itself has been theorized to function as a 'plasticity module' that can undergo structural adjustments in response to changes in synaptic input that, in turn, modify the probability of vesicle release (Wichmann and Sigrist, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the point mutation does not alter the ability of the Ca V 2.1 channel to pass calcium, it may render it insensitive to low-voltage membrane modulation during presynaptic homeostasis. Second, it was previously shown that presynaptic overexpression of a potassium channel, either Shaker or Kir2.1, blocks presynaptic homeostasis (4,72,73). If increased potassium leak prevents ENaC channel-dependent depolarization of the presynaptic membrane, then this could explain why potassium channel overexpression blocks the expression of presynaptic homeostasis.…”
Section: Homeostatic Modulation Of Presynaptic Calcium Influx Via Synmentioning
confidence: 99%
“…The emerging field of homeostatic plasticity can be subdivided into three areas that are defined by the way in which a cell responds to a perturbation, namely the homeostatic control of intrinsic excitability (1)(2)(3)(4)(5)(6)(7), neurotransmitter receptor expression (3,7), and presynaptic neurotransmitter release (8)(9)(10)(11)(12). Together, these areas represent a suite of mechanisms that confer stability to nervous system function.…”
Section: Introductionmentioning
confidence: 99%